Healthcare handoffs among lay caregivers. (18th January 2021) - Chastain, Janet; Kumar, Anil R; Nathan-Roberts, Dan
Abstract: Background: Much of home healthcare is also performed by informal caregivers. This paper seeks to add understanding to the home healthcare field, specifically studying care handoffs between informal caregivers. This study included 16 trained and 20 lay participants to determine differences due to expertise. This comparison is useful because there is a lot of published research on healthcare handoff happenings involving healthcare professionals, and the results indicate how much of the published research can be applied to care handoffs between informal caregivers. Objective: The primary objective of this study is to identify differences between lay and professional caregivers when there is uncertainty in a caregiving handoff from their fellow caregiver. Methods: The study design included between-group analysis of Expertise (layman and expert) and within-group analysis of Task Difficulty and Communication Modality. Dependent variables included willingness to ask for help, confidence in handoff instructions, confidence in the ability to complete tasks and task accuracy. Both Expertise groups were given the same four scenarios in a repeated measures study design. Results: The findings suggest statistically significant differences in how informal caregivers respond to unclear handoff instructions, where lay participants were more confident in understanding instructions, more confident in executing the tasks, less willing to ask for help and also less able to spot and resolve conflicting information compared to trained participants. Lower performance in resolving conflicting information was exhibited by the lay participants. However, when comparing with the syringes that were prepared correctly, it was observed that the accuracy of those prepared syringes was higher for lay participants than for trained participants. Conclusion: It was anticipated that lay participants would be more willing to ask for help due to lack of subject matter expertise and trained participants would be more confident in completing tasks due to their superior subject matter expertise, but the opposite was true in both cases. It was also anticipated that lay and trained participants would be equally confident of the instructions given by their fellow caregiver, yet trained participants were less confident. The results from this study have impacts on the design of instructions (often by formal caregivers) for informal caregivers.